Age-dependent phenotypic and molecular evolution of pediatric MDS arising from GATA2 deficiency - Kotmayer, Lili; Kozyra, Emilia J; Kang, Guolian; Strahm, Brigitte; Yoshimi, Ayami; Sahoo, Sushree S; Pastor, Victor B; Attardi, Enrico; Voss, Rebecca; Vinci, Luca; Kaiser, Max; Dworzak, Michael N; et al. (Blood cancer journal, 2025)
GATA2 deficiency is an autosomal dominant transcriptopathy disorder with high risk for myelodysplastic syndrome (MDS). To elucidate genotype-phenotype associations and identify new genetic risk factors for MDS, we analyzed 218 individuals with germline heterozygous GATA2 variants. We observed striking age-dependent incidence patterns in GATA2-related MDS (GATA2-MDS), with MDS being absent in infants, rare before age 6 years, and steeply increasing in older children. Among 108 distinct GATA2 variants (67 novel), null mutations conferred a 1.7-fold increased risk for MDS, had earlier MDS onset compared to other variants (12.2 vs. 14.6 years, p = 0.009) and were associated with lymphedema and deafness. In contrast, intron 4 variants exhibited reduced penetrance and lower risk for MDS development. Analysis of the somatic landscape revealed unique patterns of clonal hematopoiesis. SETBP1 mutations occurred exclusively in patients with monosomy 7 and their frequency decreased with age. Conversely, the frequency of STAG2 mutations and trisomy 8 increased with age and appeared protective against early development of advanced MDS. Overall, the majority (73.9%) of mutation-positive cases harbored monosomy 7, suggesting it serves as a major driver in malignant progression. Our findings provide evidence for age-appropriate surveillance, and a foundation for genotype-driven risk stratification in GATA2 deficiency.
Keywords: Infant; Humans; kojenec; GATA2 Transcription Factor; dítě; Child; Female; mutace; mladý dospělý; dospělí; GATA2 Deficiency; deficit GATA2; věkové faktory; Phenotype; lidé; myelodysplastické syndromy; předškolní dítě; Adult; transkripční faktor GATA2; ženské pohlaví; Male; fenotyp; Adolescent; Young Adult; Myelodysplastic Syndromes; Age Factors; Mutation; mužské pohlaví; Child, Preschool; mladiství